COST ANALYSIS WITH CRASH PROGRAM OF KEROBOKAN PARKING LOT BUILDING BALI - Dwi Cahyani Putri; Budi Witjaksana; Hanie Teki Tjendani (Asosiasi Dosen Muda Indonesia, 2024)
Kerobokan Bali Parking Building is one of the buildings that uses steel material as the main structure. The building which has a height of 13.97 meters, a width of 32.8 meters, and a length of 16.18 meters has a construction plan duration of 248 calendar days starting from July 2023. Known critical trajectory activities will be carried out a crashing program analysis with the aim of accelerating time by using one method, namely overtime work with a duration of 4 hours. Based on the analysis that has been carried out with the help of the Microsoft Project 2019 application, there are 16 lists of activities included in the critical trajectory. In writing this thesis, it will be mentioned in the form of a line code in Microsoft Project 2019, namely 569-573-579-580-581-606-585-586-590-591-595-596-600-601-602-612. In addition to knowing the list of critical path activities, this thesis also accelerates the duration with an additional 4 hours of overtime and calculates the total cost of the acceleration. After acceleration, it is known that the duration decrease is 61 days with a normal duration of 248 days to 187 days and shows a time efficiency of 0.245%. The total initial cost with normal duration is Rp 8,822,280,000.00 while if the project is accelerated, the project cost becomes Rp 8,901,216,104.5 by showing an additional cost of Rp 78,936,104.47.